Civil Society and Pro-Democracy Social Movements: Troubled Relations Within Authoritarian Regimes? - Nasibov, Murad (Frontiers in Political Science, 2021)
Civil society and social movement concepts overlap in their two core attributes, 'voluntary coming together for a common purpose' and their locus beyond the state, the market and family. Identifying this overlap as the moment of confusion in the conceptualization of civil society and social movement, this paper demonstrates in what qualities of these two core attributes they differ. To this goal, the paper distinguishes two types of solidarity: associative solidarity and collective solidarity. Consequently, by defining the linkage between solidarity and action, associative action and collective action are further proposed. Civil society and social movements are suggested to emerge on associative solidarities (and their actions), while social movements build on collective solidarities (and their actions). Furthermore, associative action is found to be progressive – that is, it consists of activities that target to gradually improve certain conditions concerning inclusion or exclusion of parts of society, or overall, the benefits of the whole. In contrast, collective action is proposed to be transgressive, as it pushes beyond boundaries within society and the boundaries of the civil code. Building on this, the rest of the paper provide theoretical proposals explaining the relationship between civil society and social movements. Finally, four types of pro-democracy movements are identified, and the proposed theoretical account on civil society-social movement is applied theoretically to one of these types – pro-democracy movement within authoritarian regimes.